THE IMPLEMENTATION OF QUIZZIZ AS AN ENGLISH LANGUAGE LEARNING ASSESSMENT TOOL - Hanani, Muhammad Dzakir Aslam; Sari, Raras Hafidha; Ambarwati, Suci (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
This study explores the implementation of Quizizz as an assessment tool for English language learning. The study highlights Quizizz's potential to enhance student engagement and motivation through its interactive, game-based format. Employing a mixed-method approach, this research involved planning and execution stages to observe the impact of Quizizz on students' understanding of